PENGARUH JARAK SARAD DAN VOLUME KAYU YANG DISARAD TERHADAP PRODUKTIVITAS TRAKTOR PENYARADAN - Dulsalam Dulsalam; Sukanda Sukanda (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
An inveatigation on the effect of alcidding diatance and •kidded log volume on the productivity of kidding tractor um carrkd out at a forest company in Jambi in 1986. Caterpillar D1 G trac ors were elected randomly and their working time and skidded log volume were obaervedthrough work time atudy. The purpoH of thia invatigation ia to find out the effect of kidding diatance and skidded log volume on the productivity of kidding tractors. The invati1Qtion coma to the fotlOwing concluaioru. 1. The owrace of skidding diatance wa 8.24 hm with standard error of 0.2tJ66 hm while the average of idded log volume IDOi 9.08 m8 with. 0.3173 m3 atandard error. J. The a productivity of skidding tractor waa 92.09 m8 hm/hour with atandard error of 6.8406 m8 hm/hour.3. The Niationahip between tractor productivity (Y) and •kidding diatance (X 1) and kidded log volur.ne (X2) can beupraaed in the li r.nultipie Ngreuion: Y - 48.1670 + 16.0704X1 + 9.6176 Xa with R2 • 0.71604. The effects of kidding diatanca and •kidded log . voluma on the productivity of •kidding tracton are aigniffcant.TM tractor productivity increaaedproportionaUy when the •kidding. diatance and •kidded• log volume increaed. It therefore recommended to make the •kidded loga as long as poaible GI far GI the tractor can handle.